Experience with luspatercept therapy in patients with transfusion-dependent low-risk myelodysplastic syndromes in real-world clinical practice: exploring the positive effect of combination with erythropoietin alfa - Jonasova, Anna; Sotakova, Slavka; Belohlavkova, Petra; Minarik, Lubomir; Stopka, Tomas; Jonas, Jan Jakub; Aghova, Tatiana; Zemanova, Zuzana (Frontiers in Oncology, 2024)
Background: Luspatercept is a novel treatment for anemic patients with lower-risk myelodysplastic syndromes (MDS) with transfusion dependence (TD) who do not respond to erythropoiesis-stimulating agents (ESA) therapy or are not suitable candidates for this treatment. We present real-world experience with luspatercept treatment. Methods: By January 2024, 54 MDS patients (33 males, 21 females), median age of 74 years (range 55-95) were treated with luspatercept ± ESA at two Charles University hematology centers. All were in the IPSS-R and IPSS-M lower risk groups (except 4 IPSS-M high). The median follow-up was 17 months (range 1-54). All patients were transfusion dependent. Thirty-five (64.8%) patients had a high transfusion burden (HTB) with ≥4 transfusion units (TU)/8 weeks, and 19 (35.2%) had a low transfusion burden (LTB) (<4TU/8 weeks). ESA were used prior to luspatercept in 45 patients. Results: Only patients who received luspatercept for ≥8 weeks (51) were assessed. Thirty-two (62.7%) patients achieved TI for ≥8 weeks, 31 (60.7%) for ≥12 weeks, 29 (56.8%) for ≥16 weeks, and 25 (49%) for ≥24 weeks. Hematologic improvement (HI) without TI was achieved in 6 patients (11.7%). Overall, HI + TI was achieved in 38 patients (74.5%). Epoetin alfa was used simultaneously in 31 patients (60.7%). In 21 (55.2%) of all responding patients, concomitant therapy with epoetin alfa improved response, with 16 TI. Optimal response required increase of luspatercept dose to 1.75 mg/kg 35 patients, with 23 responders (TI+HI). Response rates (TI) by transfusion burden was: 79% in LTB and 50% in HTB. Seventy percent of RS+ patients reached TI in contrast to only 1/5 RS-. Among 39 SF3B1 positive patients, 61.6% achieved TI. In the low and very low IPSS-M groups, 86% of patients responded (TI+HI). Luspatercept was very well-tolerated. Conclusion: We have demonstrated in real-world clinical practice that luspatercept is an effective agent, even in an unselected pretreated significantly TD MDS population. We believe that the relatively high response rate in our patients was influenced by the frequent use of a higher dose (1.75mg/kg) and especially by adding ESA to luspatercept in poorly responding patients.